2014
DOI: 10.1007/s12195-014-0359-2
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical Investigation of Soft Biological Cell Adhesion using Atomic Force Microscopy

Abstract: Mechanical coupling between living cells is a complex process that is important for a variety of biological processes. In this study the effects of specific biochemical treatment on cell-to-cell adhesion and single cell mechanics were systematically investigated using Atomic Force Microscopy (AFM) Single Cell Force Spectroscopy. Functionalised AFM tipless cantilevers were used for attaching single suspended cells that were brought in contact with substrate cells. Cell-to-cell adhesion parameters, such as maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Altering the expression of the adhesion protein does not absolutely indicate that the function of the cell-to-cell adhesion will correspondingly change. 16 The involvement of binding partners linked to the cellular architecture adds to the complexity of surface molecular interactions and hence cell adhesion is affected by changes in binding affinity, bond number and mechanical deformation. 21 In the current study, the TGF-β1 evoked reduction in E-cadherin expression was matched by a decrease in functional tethering between cells, as shown by the reduction in the number of TREs after TGF-β1 13 treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altering the expression of the adhesion protein does not absolutely indicate that the function of the cell-to-cell adhesion will correspondingly change. 16 The involvement of binding partners linked to the cellular architecture adds to the complexity of surface molecular interactions and hence cell adhesion is affected by changes in binding affinity, bond number and mechanical deformation. 21 In the current study, the TGF-β1 evoked reduction in E-cadherin expression was matched by a decrease in functional tethering between cells, as shown by the reduction in the number of TREs after TGF-β1 13 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria and assumption for applying this model to biological material are described elsewhere. [14][15][16][17] However, it has been well recognized that the Hertz model often overestimates the elasticity of cells due to substrate effects. Alternatively, the classic Hertz model which was modified by Chen to take account of the influence of the substrate to the measured elasticity may be applied for modelling the cell indentation tests.…”
Section: Cell Indentation Experimentsmentioning
confidence: 99%
“…For the adhesive contact between a cell and a polystyrene bead, the radius of MIN6 cell is typical of 12.5 μm, and the elastic modulus of cell is in the order of several hundred Pascal. The previous studies have found the value of is about 500Pa by using Hertz contact theory to fit the F-D curve of an AFM indented MIN6 cell (Siamantouras et al, 2014b). The work of adhesion ∆γ ranges from 20 to 100 μJ/m 2 , and here we assume ∆γ to be 50 μJ/m 2 (Sirghi et al, 2008).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Recording of F-d curves was conducted in liquid media (CO 2 free DMEM). To perform single cell indentation experiments, a spherical microbead (11 μm in diameter) was manually attached on the cantilever and the spring constant was then determined to be 0.059 N/m by using the thermal noise method after attachment (Siamantouras et al, 2014b). The depth of indentation was calculated by subtracting the deflection of the cantilever from the displacement of the piezo-actuator for a given spring constant (JPK Data Processing, Berlin, Germany).…”
Section: Data Preparationmentioning
confidence: 99%
See 1 more Smart Citation